Bibliometric analysis: a study of the microenvironment in cervical cancer (2000-2024) - Zhang, Yun-Tao; Wei, Yan-Ni; Liu, Chen-Chen; Yang, Mai-Qing (Frontiers in Oncology, 2025)
ObjectiveThe incidence of cervical cancer has increased in recent years. The tumor microenvironment (TME) is the local biological environment involved in tumor occurrence and development. This study aimed to conduct a comprehensive analysis of the global research on the TME in cervical cancer (CC), providing a knowledge framework in this field from a holistic and systematic perspective based on a bibliometric analysis.MethodsStudies focusing on the TME in cervical cancer were searched using the Web of Science Core Collection database. The annual output, cooperation, hotspots, research status, and development trends in this field were analyzed using bibliometric softwares (VOSviewer and CiteSpace).ResultsA total of 1,057 articles published between 2000 and 2024 were selected. The number of publications and citations has recently increased. Cooperation network analysis indicated that China holds the foremost position in research on the TME in cervical cancer with the highest volume of publications, thus exerting the greatest influence. Fudan University had the highest output. Frontiers in Oncology showed the highest degree of productivity in this field. Rofstad, Einar K. made the most article contributions and was the most co-cited author. Four clusters were obtained after a cluster analysis of the keywords: TME, cervical cancer, immunotherapy, and prognosis. Immunotherapy, human papillomavirus, and biomarkers were relatively recent keywords that attracted increasing attention from researchers.DiscussionThis bibliometric analysis provides a data-based and objective introduction to the TME of cervical cancer, and offers readers a valuable reference for future research.ConclusionsComprehensive research in this field was mainly distributed in the TME of cervical cancer through the analysis of keywords and documents. Sufficient evidence supports mechanism research and application exploration. Further research should explore new topics related to the TME of cervical cancer.